دور الشخصيات غير الإنسانية في بناء القصص القرآني - الحيوانات أنموذجًا - الكفاوين, عمر فارس (University of Eloued جامعة الوادي, 2018)
ترمي هذه الدراسة إلى الكشف عن دور الشخصيات غير الإنسانية في بناء القصص القرآني، وإبراز فاعليتها فيه، متخذة من الحيوانات أنموذجًا لذلك، حيث يشارك عدد من تلك الحيوانات في بناء أحداث ذلك القصص، وقد كان لها دور بارز فيه، مثل البقرة والكلب والعجل والذئب والحوت والثعبان والفيل والغراب والهدهد والنمل وغيرها. وتسعى الدراسة إلى توضيح مفهوم القصة القرآنية ودلالاتها، من ثم تبين دور الشخصية بشكل عام في تشكيل الحدث في تلك القصة، ثم ترصد أهمية دور الشخصيات الحيوانية في بناء أحداثها، وكيف استطاعت هذه الحيوانات بأمر الله _ جلت قدرته _ أن تكون محركة للأحداث، وتلعب دورًا مركزيًّا في بنائها، وتكون رديفة للشخصيات الإنسانية في تشكيلها، فتغدو بذلك عنصرًا مهمًا وفاعلًا من عناصرها الرئيسة. This study aims at illustrating the role of non-human characters in the construction of Quranic stories, highlighting their effectiveness, taking the animals as a model. A number of these animals participate in the construction of the events of these stories playing a prominent role, particularly the cow, dog, calf, snake, elephant, crow, hump, ants and others. The study seeks to clarify the concept of the Quranic story and its implications, showing the role of the character in general in shaping the events in that story, and therefore monitoring the importance of the role of animal figures in building their events, and how these animals were able by God’s willto play a central role in the construction of events, being a companion to the human figures in its formation, thus becoming an important and active element of its main construction
The role of non-human characters in building Quranic stories - Animals as model
مجلة البحوث والدراسات المجلد 15 العدد02 جامعة الوادي
Keywords: القصص القرآني، الشخصيات، الحيوانات; Quranic stories; characters; animals